From Digital Knowledge Into Digital Sovereignty - Gherbi, Said; Tamghart, Ismahan (University of Eloued جامعة الوادي, 2024)
Abstract: The concept of sovereignty has evolved since its inception by the French thinker John Bodin, from geographical sovereignty, which was manifested after the Treaty of Westphalia in 1648 in demarcating the borders between European countries, to digital sovereignty, represented by the attempt of major countries to protect their data from hacking and their cyber security from threat, especially all their commercial movement The economic and even military sectors are now controlled by computers, chips, and websites that are threatened by piracy. China is one of the world's leading countries in protecting its digital data, achieving great numbers in the path of digital sovereignty.
Data Protection In China As A Model
Keywords: Digital literacy; digital sovereignty; data protection; China; cyber security